Reinterpreting Religion in the Digital Age: Theology, Ethics, and Christian Education - Boiliu, Esti Regina; Jura, Demsy; de Carvalho, António Oliveira (Didache: Journal of Christian Education, 2025)
The rapid advancement of digital technology has transformed how faith is practiced and how Christian Religious Education is delivered, necessitating a theological reinterpretation of religious formation in digital contexts. This study aims to develop a theoretical framework that integrates theology, ethics, digital literacy, and spirituality to guide Christian education in the digital era. Employing a qualitative literature review method, the study analyzes scholarly works on digital theology, education, and ethics to examine how digital environments shape faith formation, moral reasoning, and community engagement. The findings reveal that digital media functions not merely as a communication tool but as a formative environment influencing spiritual identity and ethical behavior. The proposed digital Christian Religious Education model emphasizes four interrelated dimensions: theology as the foundation of faith, ethics as responsible digital citizenship, digital literacy as critical engagement, and spirituality as holistic formation across physical and virtual spaces. This study contributes to global discourse by offering an integrative and contextual approach that empowers Christian educators to foster authentic spiritual growth and responsible digital discipleship in an increasingly networked world.